the Effect of foliar feeding with the organic fertilizer "Sana" and seaweed extract "Algaton" on the set percentage of the apple variety “Grany Smith” and on some indicators of vegetative growth and physical characteristics of its fruits. - كوردموسيان, جانو; جرجس مخول (Latakia University Journal -Biological Sciences Series, 2024)
The research was carried out during the 2023 season on “Grany Smith” apple trees, 20 years old, grafted onto seedstock and planted with dimensions of 5 x 5 meters in the Kassab region of Latakia Governorate, at an altitude of 800 meters above sea level. The study aimed to determine the effect of foliar feeding with the organic fertilizer “Sana.” "Algaton" seaweed extract in the percentage of set flowers, the percentage of remaining fruits, the area of the leaf surface area, its total chlorophyll content, and the average weight and size of the fruit. The experiment included (9) treatments, and each treatment had three replicates. The results showed the positive effect of foliar feeding with Sana organic fertilizer and Algaton marine algae extract on the studied traits. The ninth and eighth treatments (Algaton 2.5 ml/liter + Sana 1.5 ml/liter) and (Algaton 2.5 ml/liter + Sana 1 ml/liter) achieved the highest percentage of set flowers (51.29%, 49.34%), respectively, while the lowest value was in Control 37.50%. The results of the statistical analysis showed that the ninth mixing treatment was superior to the rest of the treatments in which the two fertilizers were used individually or in a mixture, while the eighth mixing treatment was superior to the spraying treatments with the two fertilizers separately. The ninth treatment gave the highest value for the leaf surface area, 62.74 cm2, and was significantly superior to the control, 49.54 cm2, and to the rest of the treatments, except for the eighth treatment. The ninth treatment recorded the largest value for the average weight and size of the fruit (215.9 g, 267 cm3), and the lowest value was for the control (146.5 g, 169.8 cm3). The results of the statistical analysis showed that the ninth treatment was superior to the control and to the rest of the treatments except the eighth treatment.